Spatial.io in English Language Learning: Non-English Majors’ Perceptions of Virtual Space in the Metaverse - Nita Sari Narulita Dewi; Yusup Supriyono; Ratu Sarah Pujasari; Muhammad Adlan Faishal; Luis Luigi Eugenio A; Santiana Santiana (Teacher Training and Education Faculty, Widya Gama Mahakam Samarinda University, 2026)
Background: Despite the promise of immersive education for metaverses, empirical evidence regarding the specific role in English language learning for non-English majors remains scarce. This study addresses the gap by examining students’ perceptions of the metaverse platform, Spatial.io, to inform more inclusive teaching strategies. Methodology: This study employed a qualitative case study design. Semi-structured interviews were conducted with four non-English major students selected to provide insight into early user experiences, and thematic analysis was utilized to interpret the interview data. Findings: Drawing on the Technology Acceptance Model (TAM), the analysis revealed three key themes. First, regarding perceived usefulness, participants reported that the metaverse enhanced interactivity, collaboration, and English language skills through immersive features. Second, perceived ease of use attributed to the platform’s flexibility and intuitive interface. However, significant challenged identified regarding technical infrastructure, internet instability and device compatibility, which hindered equitable access. Conclusion: The metaverse shows promise as a supplementary tool for enhancing English language skills development. However, because this study only involved a small group of students, these results are preliminary. Future implementation implies the needs for improved infrastructure and hardware compatibility to ensure inclusive learning environment. Originality: This study provides a closer look at how non-English majors perceive the metaverse (Spatial.io), offering early insight into how this technology might change language education before it is widely adopted.